Prognostic value of IGF-1R in lung cancer: A PRISMA-compliant meta-analysis - Xu, Jun (Medicine (Baltimore), 2019)
BACKGROUND: Insulin-like growth factor receptor 1 (IGF-1R) is a key player in a wide array of pathological processes, while the prognostic role of IGF-1R in lung cancer remains controversial. METHODS: We conducted a meta-analysis to evaluate the prognostic value of IGF-1R in lung cancer. We searched for recent studies on the expression of IGF-1R and extracted prognostic lung cancer data from the articles. RESULTS: Eventually, 22 studies with 3859 patients were analyzed in our meta-analysis. Hazard ratios (HRs) and their 95% confidence intervals (CIs) were used to quantify the ability of IGF-1R to predict survival. The results indicated that IGF-1R positive expression was associated with an unfavorable disease-free survival (DFS) in non-small cell lung cancer (NSCLC) patients on univariate analysis (HR = 1.24, 95% CI: 1.00–1.55, P = .054) and multivariate analysis (HR = 1.49, 95% CI: 1.01–2.21, P = .045), but there was no significant difference in the relationship between IGF-1R positive expression and overall survival (OS) on univariate analysis (HR = 1.04, 95% CI: 0.86–1.25, P = .712) and multivariate analysis (HR = 0.89, 95% CI: 0.57–1.39, P = .602). IGF-1R mRNA expression related to OS was obtained in 2 studies, with the pooled HR being 1.663 (95% CI: 1.071–2.583, P = .024). For IGF-1R expression and small cell lung cancer (SCLC), the conclusion was not statistically significant, with the pooled HR being 1.22 (95% CI: 0.66–2.27, P = .524). CONCLUSIONS: Our results indicate that high expression of IGF-1R predicts poor DFS in NSCLC, yet it does not predict poor OS in NSCLC and SCLC. IGF-1R may be a useful predictor of outcomes in patients with NSCLC.